Challenges in using authentic assessment in 21st century ESL classrooms - Muhammad Noor Abdul Aziz; Nurahimah Mohd Yusoff; Mohd Faiz Mohd Yaakob (Institute of Advanced Engineering and Science, 2020)
This paper seeks to explore the challenges faced by excellent teachers in preparing for authentic assessment in their English as a Second Language (ESL) classrooms. This qualitative case study involving six excellent teachers was based on purposive sampling. Data sources in this study used classroom observation and a series of semi-structured interviews with the excellent teachers. Thematic analysis was used to identify emerging themes from the codes gathered from the interviews and observations. Data showed that excellent teachers faced multiple challenges prior to preparing for authentic assessment. They have also been using variations of authentic assessment to help children in their learning besides accurate documentation and extensive reading from around the globe to equip themselves with the current knowledge. Since there is no clear guideline for teachers who practice authentic assessment in their classes, this study provided some insights on the preparations and the use of authentic assessment as part of their teaching and learning process.